Left Ventricular Assist Device Driveline Infections: The Achilles' Heel of Destination Therapy. (October 2015) - Angud, Marc
Abstract : Heart failure is a chronic progressive disease that affects millions of people in the United States. Although medical management of heart failure has helped improve quality of life and survival, end-stage heart failure ultimately requires a heart transplant or long-term left ventricular assist device (LVAD) support. With more patients awaiting transplant, the demand for hearts outweighs the supply of donor hearts. The use of LVADs is increasing in patients with advanced heart failure as a treatment option for those awaiting a heart transplant or as a long-term solution if they are ineligible for a transplant. Although the LVAD is a marvel of modern medicine, infection is a cause of concern because today's LVADs are powered externally through a percutaneous driveline that can be a major source of infection.